Las dimensiones del emprendimiento empresarial: la experiencia de los programas cultura e y fondo emprender en Medellín. (2008)
A manager is a person who has a managerial guidance of creating a company, to innovate; it has a comparative advantage in making decisions, as he gains more knowledge about the events and opportunities and is the one who takes the risks and profi ts (Pickle y Abrahamson, 1990). Being an entrepreneur is having the ability to create something new or to give a different use to an existing element, as well as generating an impact on the lives of the comunity in which it inhabits (Formichella, 2004). He is suffi ciently fl exible to adapt ideas and has the creativity to turn every event into an opportunity. It can be said that a manager can and must be an entrepreneur but not necessarily an entrepreneur has to be a manager (Gartner, 1989).In Medellín, entrepreneurship programs have been developed over the past 5 years in order to generate employment and create an entrepreneurial culture. This paper shows that in order to develop these programs, an understanding of the entrepreneurship dimensions (the individual, the environment and the processes), and how these interact with each other is required. This Research Newsletter presents the following topics: 1) Method created to carry out the research; 2) Characteristics of entrepreneurship programs according to the individual dimensions, as well as processes and environment 3) frame of reference for entrepreneurship; 4) Descriptive, factorial and content analysis of the interviews to entrepreneurs and; 5) conclusions